2012
DOI: 10.2168/lmcs-8(1:15)2012
|View full text |Cite
|
Sign up to set email alerts
|

Two-Variable Logic with Two Order Relations

Abstract: Abstract. It is shown that the finite satisfiability problem for two-variable logic over structures with one total preorder relation, its induced successor relation, one linear order relation and some further unary relations is EXPSPACE-complete. Actually, EXPSPACEcompleteness already holds for structures that do not include the induced successor relation. As a special case, the EXPSPACE upper bound applies to two-variable logic over structures with two linear orders. A further consequence is that satisfiabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…A few works such as [31], [35], [36] are on words, while in most applications we need to consider trees. Moreover, these works are incomparable to some interesting existing formalisms [17], [6], [2], [12], [24], [14], [29] known to be able to capture various interesting scenarios common in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few works such as [31], [35], [36] are on words, while in most applications we need to consider trees. Moreover, these works are incomparable to some interesting existing formalisms [17], [6], [2], [12], [24], [14], [29] known to be able to capture various interesting scenarios common in practice.…”
Section: Introductionmentioning
confidence: 99%
“…In [35] it is shown that the satisfaction problem of the logic FO 2 (<, ≺) on words is decidable. This logic is incomparable with our model.…”
Section: Introductionmentioning
confidence: 99%
“…Satisfiability and finite satisfiability of C 2 with a single equivalence relation was shown to be NEXPTIME-complete, while C 2 with two equivalence relations is undecidable [26]. Decidability of extensions of F O 2 with successor relations, order relations, and equivalence relations without counting were studied [13], [16], [17], [20], [21], [30].…”
Section: The Two-variable Fragment and Alcqiomentioning
confidence: 99%
“…Most of them turn out to have undecidable satisfiability problem (see, e.g., [10,16]). On the positive side, FO 2 remains decidable when extended by counting quantifiers [9,26,27], counting quantifiers and two forests accessible by their successor relations [5] (finite satisfiability only), a linear order [25] (or, in the case of finite satisfiability, even two linear orders, subject to some further restrictions on the signatures, see [29]), one or two equivalence relations [18,19], one transitive relation [31] (general satisfiability only, the case of finite models is open).…”
Section: Related Workmentioning
confidence: 99%